PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI INSPEKTORAT KABUPATEN PADANG LAWAS SUMATERA UTARA - Daulay, Lili Andayani; Savitri, Shela Indah (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of the physical work environment and work discipline on employee performance at the Padang Lawas Regency Inspectorate Office, North Sumatra. This research uses Quantitative methods with an associative approach. The sampling technique used saturated sampling and obtained a sample of 72 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis testing. The results of this study are that the physical work environment has a significant effect on employee performance with a determination value of 26.0% and hypothesis testing obtained t count> t table or (4.528>1.667). Work discipline has a significant effect on employee performance with a determination coefficient of 23.0% and hypothesis testing obtained t count> t table or (2,480>1,667). The physical work environment and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 16.214 + 0.591 X1 + 0.011 X2. The coefficient of determination is 48.0% while the remaining 52% is influenced by other factors. Hypothesis testing obtained the value of F count> F table or (10.313> 3.13).